Proses Membaca Kata CVC Bahasa Inggris Menggunakan Metode Fonik - Ni Luh Desy Suari Dewi (Journal on Education, 2023)
English has now begun to be taught in early childhood so the learning process is of course different. Early childhood English learning is usually taught through English sounds. From these sounds they will learn to read simple words (CVC) as well as learn their meaning. In this study, the stages of introduction to English phonics in the learning process of reading CVC will be discussed. This study is a qualitative descriptive study that aims to explain the stages of introduction of English phonics in reading simple English words (CVC) to 15 students who are studying English Phonics with an age range of three to seven years. This research uses a synthetic phonics approach whose learning focuses on words separated into the smallest part of the unit, namely sound (Phajane, 2014). There were 8 consonant sounds /s/, /t/, /p/, /n/, /k/, /m/, /r/, /h/ and 2 vowel sounds /a/, /i/ introduced in this study. The results of this study show that the stages of English phonics recognition in the learning process of reading CVC are sounding letters, spelling and mixing sounds into meaningful words. The results of this study also show that there are two letters that not all students can sound well. The letter is the consonant letter c with the pronunciation /k/ and the vowel a with the pronunciation /æ/.